Sistem Informasi Pariwisata di Kabupaten Magetan Berbasis Web dan Mobile - Kusuma, Rinto Hadi Tedja, Umi Fadlilah,ST.M.Eng (2017)
Magetan District is located in the region of Ex - Madiun Residency directly adjacent to the western part of Central Java. Magetan potentially interesting attractions to visit, especially with the cold nature mountain Lawu. But, just because ineffectively of information about tourism in a region will decreasing of tourist's interest to visit that place. More information about tourism only could be access by offline or by following tour group.Based on the problems above the writer makes a system application about tourism information. So, in this research the writer takes a title Implementasi of Information System About Tourism in Magetan Regency with a Web and Mobile Basic. Direct observation and literature studying were used in this observation. Tourism Information System of Wonogiri Regency with a Web Basic was made in two version. First version is website version was made using PHP language program with MYSQL database and second version is mobile version was made using LUA language program. The result of implementation Final Project is a website and mobile application have a tourism location information of Magetan.